The Role of Strategy Flexibility, Competitive Intelligence, Organizational Innovation, and Entrepreneurship Leadership in Increasing Agility of MSME Troso Woven Fabric - Ahmad Fika Syauqiy; I Made Bayu Dirgantara (Budapest International Research and Critics University, 2022)
This research aims to identify factors that can increase the organizational agility of MSMEs (micro, small, and medium enterprises), especially in the Troso woven fabric industry in Jepara Regency, Central Java, Indonesia. We examine several variables that have been shown to affect large-scale business agility in various industries. So, this research reveals the consistency of some of these factors in increasing the agility of a business organization, large or small. Data were collected from 14 2 active business actors in the Troso woven fabric SMEs as our sample for testing the proposed research model, using a questionnaire which is then processed and analyzed using regression analysis. As a result, we find that the proposed 4 independent variables, strategic flexibility, competitive intelligence, organizational innovation, and entrepreneurial leadership, all affect increasing MSME agility.